Features of diagnosis and treatment of spleen abscesses. - O. B. Kutovoy; O. A. Klishyn; S. O. Kosulnikov; K. V. Kravchenko; S. O. Tarnopolskiy; M. V. Lohvynenko (Medičnì Perspektivi, 2020)
The purpose of the study is to clarify the causes, features of clinical manifestations, to evaluate the results of diagnosis and surgical treatment of patients with sepleen abscesses. The article presents data on the results of diagnosis and treatment of 19 patients with spleen abscesses who were treated at the Surgery Department of the Dnipropetrovsk Regional Clinical Hospital named after I.I. Mechnikov, from 2006 to 2018. A comparative analysis of the etiological factors of spleen abscesses among a selected group of patients was carried out. It was established that among the causes of spleen abscesses according to our data were: bacterial endocarditis, purulent diseases of the pancreas, trauma, simple cysts, portal vein thrombosis. When analyzing the results of inoculation of the contents of abscesses, it was determined that E.Coli (26.3%), St. Epidermalis (21.1%), Ac.Baumani (10.5%) and P. Aeruginosa 21.1%) occur the most often. For the diagnosis of spleen abscesses, general clinical, biochemical, and hardware methods of investigation (computed tomography, ultrasound examination of the abdominal organs) were used. The treatment of spleen abscesses was complex and included conservative therapy and surgical methods. As a surgical treatment minimally invasive, laparoscopic, as well as open techniques were used. The main surgical method was percutaneous drainage with ultrasound monitoring (42.1%). Relapse of abscess with this treatment option in the remote period was detected in 1 (5.6%) patient. In 5 (26.3%) cases patients with spleen abscesses underwent laparotomy and splenectomy. Laparoscopy was performed in 2 (10.5%) patients with spleen abscesses, operations were completed by opening, debridement and drainage of the abscess cavity and abdominal cavity. Fatal cases were not observed in the treatment of spleen abscesses. The combination of conservative therapy (using etiotropic antibacterial therapy) and surgical treatment (a combination of minimally invasive and laparoscopic techniques) allowed to achieve good treatment results. The number of complications was 15.8%.